Data Management in Digital Twins for the Oil and Gas Industry: beyond the OSDU Data Platform - B. Correia, Jaqueline; Rodrigues, Fabrício; Santos, Nicolau; Abel, Mara; Becker, Karin (Journal of Information and Data Management, 2022)
Competitiveness in the Oil and Gas (O&G) sector has required high technological investments for datacentric decisions. One of the trends is the adoption of Digital Twins (DTs), which use virtual spaces and advanced analytical services to monitor and improve physical spaces. Central to the interconnection of these systems is a Data Fusion Core (DFC) component, which provides data management capabilities. Although the literature has proposed data management functionality in the scope of specific O&G DT applications, different joint efforts towards standardization can be found to deal with data integration and interoperability in the industry. The Open Subsurface Data Universe (OSDU) data platform is an initiative by several partners members of The Open Group consortium created to eliminate data silos in the O&G ecosystem and leverage innovation through a data-driven approach. In this article, we look at the convergence of this effort in providing data management functionalities for digital twins, highlighting strengths, gaps, and opportunities. We investigated the extent to which the OSDU data platform meets the needs of a DFC implementation, with a focus on interoperability, integration, governance, and data lineage. We also propose additional resources for data management in this context, namely data enrichment, workflows, and data lineage. Our main contributions are: (i) analysis of possible data management capabilities for creating a working DFC for an O&G DT and (ii) initial ideas on the complementary role of OSDU data representation and ontologies and how this semantic enrichment can be leveraged in a DFC of a DT.